INKLUSI KEUANGAN PETANI: MENJEMBATANI LITERASI KEUANGAN MELALUI PERBANKAN DAN MEKANISME INFORMAL - Lailatul, Nurul; Vitriyah, Nurul Lailatul (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study analyzes the financial literacy and inclusion of farmers in Indonesia. a qualitative desk study method. The study examines the factors that influence financial literacy and barriers to financial inclusion, as well as the role of banking and informal mechanisms in improving farmers' welfare (Anwar et al., 2020, p. 125; Rahmah & Nurhayati, 2024, p. 414). The results show that farmers' finansial literacy is moderate, with the lowest level of financial knowledge, while their attitudes and behaviors are better (Nadia et al., 2024: 66). The main barriers include limited access to banks, low literacy, and distrust of formal institutions; thus, farmers still rely on informal mechanisms (Rahmah & Nurhayati, 2024: 420). Community-based Literacy training and digital financial service innovations, especially Sharia-based ones, are effective in improving farmers' financial inclusion and decision-making. in improving farmers' financial inclusion and decision-making (Budastra et et al., 2022: 1174; Buono et al., 2023: 3954). The integration of finansial literacy and inclusion is important for farmers' welfare through the collaboration of formal banking, micro institutions, and informal mechanisms is important for farmers' well-being (Sibuea et al., 2022: 152; Wardhono et al., 2018: 20). et al., 2018: 20). Recommendations include expanding access to services, strengthening training, and developing adaptive digital innovations. This research provides an empirical basis for policymakers and practitioners to design sustainable financial inclusion programs.